Site Selection for a Network ofWeather Stations Using AHP and Near Analysis in a GIS Environment in Amazonas, NW Peru - Rojas Briceño, Nilton B.; Salas López, Rolando; Silva López, Jhonsy Omar; Oliva Cruz, Manuel; Gómez Fernández, Darwin; Terrones Murga, Renzo E.; Iliquin Trigoso, Daniel; Barrena Gurbillón, Miguel; Barboza Castillo, Elgar (MDPI, 2022)
Meteorological observations play a major role in land management; thus, it is vital to properly plan the monitoring network of weather stations (WS). This study, therefore, selected ‘highly suitable’ sites with the objective of replanning the WS network in Amazonas, NW Peru. A set of 11 selection criteria for WS sites were identified and mapped in a Geographic Information System, as well as their importance weights were determined using Analytic Hierarchy Process and experts. A map of the suitability of the territory for WS sites was constructed by weighted superimposition of the criteria maps. On this map, the suitability status of the 20 existing WS sites was then assessed and, if necessary, relocated. New ‘highly suitable’ sites were determined by the Near Analysis method using existing WS (some relocated). The territory suitability map for WS showed that 0.3% (108.55 km2) of Amazonas has ‘highly suitable’ characteristics to establish WS. This ‘highly suitable’ territory corresponds to 26,683 polygons (of ≥30 × 30 m each), from which 100 polygons were selected in 11 possible distributions of new WS networks in Amazonas, with different number and distance of new WS in each distribution. The implementation of this methodology will be a useful support tool for WS network planning.